Intensive sea urchin harvest rescales Paracentrotus lividus population structure and threatens self-sustenance - Ruberti,Nicole; Brundu,Gianni; Ceccherelli,Giulia; Grech,Daniele; Guala,Ivan; Loi,Barbara; Farina,Simone (PeerJ, 2023)
The harvest of the edible sea urchin Paracentrotus lividus is intensively practiced in some regions of the Western Mediterranean Sea. The removal of the largest individuals can determine an overall reduction in population size and a size class truncation that can lead to a drastic drop the self-sustenance. The aim of this study is to evaluate the variability of the population reproductive potential across 5 years in one of the main harvest hotspots of Sardinia (Western Mediterranean Sea). The breeding stock consists of commercial and under-commercial size individuals which were sampled on a monthly basis to estimate their GonadoSomatic Index (GSI) and the Individual Gamete Output (IGO). In addition, the reproductive potential of the population—Total Gamete Output (TGO)—was calculated across the 5-year period in relation with the variation of the density of the breeding stock. During the last year, the reproductive potential was also estimated in a well-conserved population of a nearby Marine Protected Area. No significant variability in GSI and IGO was found over the 5 years nor when compared with the ones of protected population in the last year. However, the intensive harvest drastically rescaled the population body-size: although density of the commercial size class remained low, density of the under-commercial size-class halved from the beginning to the end of the study. Accordingly, the proportional decrease of their gamete output contribution led to a 40% loss of the reproductive potential of the whole population in the 5-year period. Interestingly, despite the loss of reproductive potential due to the decrease of the breeding stock density, the average values of IGO slightly increased across the years leading to the highest Annual Gamete Output (AGO) during the fourth year of sampling. This positive pattern could suggest a mechanism of reproductive investments of the survivors in terms of gonad production rate or increase in spawning intensity. This work provides evidence of the direct effect of size-selective harvesting on the rapid loss of population self-sustenance. Furthermore, it lays new prospective for future research of the indirect effects of the rescaling population body-size in functional traits of the sea urchin P. lividus and that could become important for both, sustainable exploitation and ecosystem conservation management.
Keywords: Ecology conservation; Gonadosomatic index; Reproductive potential; Sea urchins; Fishing management; Sea urchin overharvesting; Size-selective harvesting